Piezoelectric element
The piezoelectric element addresses stress concentration issues in lead-free piezoelectric ceramic materials by incorporating stress relaxation portions at the outer edge of the internal electrodes, thereby enhancing durability and reliability.
Patent Information
- Application Number
- JP2023155480
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
Lead-free piezoelectric ceramic materials are less likely to deform and have greater rigidity compared to PZT, leading to stress concentration near the corners of internal electrodes, which can result in cracks and reduced durability.
A piezoelectric element with a lead-free piezoelectric ceramic composition and internal electrodes alternately stacked, featuring stress relaxation portions at the outer edge that connect adjacent sides and are located at the center of the internal electrode from the virtual vertex, effectively relieving stress concentrations.
The proposed configuration effectively relieves stresses near the corners of internal electrodes, reducing the likelihood of cracks and enhancing the durability and reliability of the piezoelectric element.
Smart Images

Figure 2025047156000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a piezoelectric element. [Background technology]
[0002] Traditionally, PZT (lead zirconate titanate) has been widely used as a ceramic that exhibits piezoelectricity. However, because PZT contains lead, its environmental impact has been a concern, and in recent years, development of lead-free piezoelectric ceramic materials has been progressing. In general, piezoelectric bodies such as lead-free piezoelectric ceramic materials are required to have high insulation properties, regardless of whether they are lead-containing or lead-free. Piezoelectric bodies expand and contract in response to the applied voltage, and stacked piezoelectric actuator elements with a structure in which piezoelectric bodies and internal electrodes are alternately stacked in multiple layers have been developed and put to practical use.
[0003] In a multilayer piezoelectric actuator element, the portion of the piezoelectric body sandwiched between the internal electrodes becomes a piezoelectrically active portion, and the portion not sandwiched between the internal electrodes becomes a piezoelectrically inactive portion. As a result, the displacement distribution changes significantly at the boundary between the piezoelectrically active portion and the piezoelectrically inactive portion, and stress is concentrated in this portion. This stress concentration increases the possibility of cracks occurring when the element is driven for a long period of time, reducing durability.
[0004] To relieve such stress, a multi-layer piezoelectric actuator in which a stress relief layer is formed is known. For example, the multi-layer piezoelectric actuator described in JP 2011-181958 A (Patent Document 1 below) has piezoelectric ceramic layers and internal electrodes alternately laminated, and each internal electrode is connected to an external electrode. This multi-layer piezoelectric actuator has a structure in which, among 10 to 40 piezoelectric ceramic layers, there is a piezoelectric ceramic layer in which a stress relief layer is formed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-181958 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, because lead-free piezoelectric ceramic materials are less likely to deform and have greater rigidity than PZT, simply providing a stress relaxation layer may not be sufficient to relieve stress. In particular, there is a risk of cracks occurring in the piezoelectric ceramic layer due to stress concentration near the corners of the internal electrodes. [Means for solving the problem]
[0007] The piezoelectric element of the present disclosure is a piezoelectric element in which piezoelectric bodies formed of a lead-free piezoelectric ceramic composition having piezoelectricity and internal electrodes are alternately stacked in multiple layers, and the outer edge of a cross section of the piezoelectric element cut in a direction perpendicular to the stacking direction of the internal electrodes has a plurality of sides and a plurality of stress relief portions connecting each of adjacent pairs of the sides, and the stress relief portions are formed so as to be located closer to the center of the internal electrodes than the virtual vertex, when the point where the extensions of each of the adjacent pairs of the sides intersect is defined as a virtual vertex. Effect of the Invention
[0008] According to the present disclosure, it is possible to reduce stress in the vicinity of the corners of the internal electrodes of the piezoelectric element. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic configuration of the piezoelectric element of the first embodiment. [Diagram 2] FIG. 2 is a perspective view showing a part of the laminate of FIG. 1 exploded in the lamination direction. [Diagram 3] FIG. 3 is a cross-sectional view showing a cross section of an internal electrode of the piezoelectric element of embodiment 1 taken in a direction perpendicular to the lamination direction. [Figure 4] FIG. 4 is a cross-sectional view showing a cross section of an internal electrode of the piezoelectric element of the second embodiment cut in a direction perpendicular to the lamination direction. [Diagram 5]FIG. 5 is a cross-sectional view showing a cross section of an internal electrode of the piezoelectric element of the third embodiment cut in a direction perpendicular to the lamination direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Overview of the embodiment] First, embodiments of the present disclosure will be listed and described. (1) The piezoelectric element of the present disclosure is a piezoelectric element in which piezoelectric bodies formed of a lead-free piezoelectric ceramic composition having piezoelectric properties and internal electrodes are alternately stacked in multiple layers, and the outer edge of a cross section of the piezoelectric element cut in a direction perpendicular to the stacking direction of the internal electrodes has a plurality of sides and a plurality of stress relief portions connecting each of adjacent pairs of the sides, and the stress relief portions are formed so as to be located closer to the center of the internal electrodes than the virtual vertex, when the virtual vertex is defined as the point where the extensions of each of the adjacent pairs of the sides intersect.
[0011] The piezoelectric body sandwiched between an internal electrode and an adjacent internal electrode becomes a piezoelectric active part, and the part not sandwiched between the two internal electrodes becomes a piezoelectric inactive part. It is known that the displacement distribution in the boundary between the piezoelectric active part and the piezoelectric inactive part changes significantly, especially near the corner of the internal electrode, and stress is concentrated in this part. In addition, a piezoelectric body formed of a lead-free piezoelectric ceramic composition is less likely to deform and has a higher rigidity than PZT, so it is thought that stress is more concentrated there. According to the above configuration, the stress relaxation parts connecting each pair of adjacent sides in the cross section of the internal electrode are located closer to the center of the internal electrode than the virtual vertices corresponding to the conventional internal electrode corners, so that the stress can be relaxed by eliminating the internal electrode corners.
[0012] (2) It is preferable that the stress relaxation portion is configured with an outwardly convex curved surface. Since the stress relaxation portion is configured with an outwardly convex curved surface, the stress can be easily dispersed over the entire curved surface.
[0013] (3) It is preferable that the stress relaxation portion is configured with an inwardly convex curved surface. Since the stress relaxation portion is configured with an inwardly convex curved surface, the stress can be easily dispersed over the entire curved surface.
[0014] (4) The stress relaxation portion is preferably configured with a C-surface forming a tapered shape. Since the stress relief portion is composed of C-faces, the stress is easily distributed over the entire C-face.
[0015] [Details of the embodiment] Specific examples of the present disclosure will be described below with reference to the drawings. Note that the present disclosure is not limited to these examples, but is defined by the claims, and is intended to include all modifications within the meaning and scope of the claims.
[0016] The piezoelectric element of the present embodiment can be widely used for vibration detection, pressure detection, oscillation, piezoelectric device, etc. For example, it can be used in sensors (knock sensors, combustion pressure sensors, etc.) that detect various vibrations, piezoelectric devices such as vibrators, actuators, haptics, buzzers, filters, high-voltage generators, micro power sources, various driving devices, position control devices, vibration suppression devices, fluid discharge devices (paint discharge, fuel discharge, etc.), etc.
[0017] <Embodiment 1> A first embodiment of the present disclosure will be described with reference to Figures 1 to 3. As shown in Figure 1, a piezoelectric element 1 includes a laminate 5 formed by alternately laminating a piezoelectric body 2 formed of a lead-free piezoelectric ceramic composition and conductive internal electrodes 3 and 4. Note that, although the number of layers in the laminate 5 is omitted and shown as small in Figure 1, an actual piezoelectric element 1 has a large number of layers.
[0018] [Piezoelectric material 2] The piezoelectric body 2 is a lead-free piezoelectric ceramic composition having a main phase formed of a first crystal phase consisting of an alkali niobate-based perovskite oxide, and a subphase including a second crystal phase consisting of an M-Ti-O-based spinel compound.
[0019] In this specification, the term "spinel compound" includes both a normal spinel compound having a normal spinel crystal structure and an inverse spinel compound having an inverse spinel crystal structure. The element M in the M-Ti-O spinel compound is a monovalent to tetravalent metal element.
[0020] The ratio of the second crystal phase in the lead-free piezoelectric ceramic composition is more than 0 volume % and not more than 10 volume %, with the remainder being the first crystal phase. In this specification, the first crystal phase is also referred to as the "main phase", and the crystal phase other than the main phase is referred to as the "subphase".
[0021] The alkali niobate perovskite oxide of the first crystal phase is represented by the following composition formula (1).
[0022] (K a Na b Li c C d ) e (D f E g )O h ...(1) However, element C is at least one of Ca (calcium) and Ba (barium), element D is at least one of Nb (niobium), Ti (titanium), and Zr (zirconium), including at least Nb, and element E is at least one of Fe (iron), Co (cobalt), Zn (zinc), and Mg (magnesium).
[0023] In the above composition formula (1), K (potassium), Na (sodium), Li (lithium), and element C are arranged at the so-called A site of the perovskite structure, and elements D and E are arranged at the so-called B site of the perovskite structure.
[0024] The values of the coefficients a, b, c, d, e, f, g, and h in the above composition formula (1) are those that establish a perovskite structure and that are suitable for the electrical or piezoelectric properties of the lead-free piezoelectric ceramic composition (particularly the piezoelectric constant d 33 ) and also from the viewpoint of keeping the sintering temperature low during production.
[0025] Specifically, the sum of the coefficients a, b, c, and d of the elements at the A site is 1 (i.e., a + b + c + d = 1).
[0026] Regarding the coefficients a, b, and c, it is preferable that 0 ≤ a < 1, 0 ≤ b < 1, and 0 ≤ c < 1, respectively. However, it is preferably not the case that a = b = c = 0 (i.e., a lead-free piezoelectric ceramic composition containing none of K, Na, and Li). The coefficients a and b of K and Na are typically 0 < a ≤ 0.6 and 0 < b ≤ 0.6. The coefficient c of Li may be 0 (zero), but 0 < c ≤ 0.2 is preferable, and 0 < c ≤ 0.1 is more preferable.
[0027] The coefficient d of element C may be 0 (zero), but 0 < d ≤ 0.2 is preferable, and 0 < d ≤ 0.1 is more preferable.
[0028] The coefficient e with respect to the entire A site can be any value as long as the object of the present disclosure is not impaired. As the coefficient e, 0.80 ≤ e ≤ 1.10 is preferable, 0.84 ≤ e ≤ 1.08 is more preferable, and 0.88 ≤ e ≤ 1.07 is even more preferable.
[0029] The sum of the coefficients f and g of the elements D and E at the B site is 1 (i.e., f + g = 1). As long as the object of the present disclosure is not impaired, it is preferable that the coefficient f of element D is not 0 (zero), and the coefficient g of element E may be 0 (zero).
[0030] The coefficient h of oxygen (O) can be any value at which the first crystal phase can maintain a perovskite-type crystal structure. A typical value of the coefficient h is about 3, and 3.0 ≤ h ≤ 3.1 is preferable. The value of the coefficient h can be calculated from the electrical neutrality condition of the composition of the first crystal phase. However, as the composition of the first crystal phase, a composition slightly deviated from the electrical neutrality condition is also acceptable.
[0031] The alkali niobate perovskite oxide represented by the above composition formula (1) is an oxide whose main metal components are K, Na, and Nb, and is therefore called "KNN" or "KNN material." Such alkali niobate perovskite oxides have excellent piezoelectric and electrical properties.
[0032] The M-Ti-O spinel compound of the second crystal phase is an oxide containing element M (a monovalent to tetravalent metal element) and Ti (titanium), and is represented, for example, by the following composition formula (2).
[0033] M x TiO y ...(2) Here, the element M is a monovalent to tetravalent metal element. Specifically, the element M is at least one element selected from the group consisting of Li, Fe, Co, Zn, Zr, and Mg.
[0034] The coefficients x and y are relative values when the Ti content is taken as 1. In order for the second crystal phase to form a spinel compound, it is preferable that the coefficient x satisfies 0.5≦x≦5.0. The coefficient y may be any value that forms a spinel compound, but it is preferable that the coefficient y satisfies, for example, 2≦y≦8.
[0035] The second crystal phase composed of a spinel compound stabilizes the structure of the first crystal phase, so that a lead-free piezoelectric ceramic composition having excellent piezoelectric properties can be obtained. From the viewpoint of piezoelectric properties, it is preferable to adopt the second crystal phase represented by the composition formula M2TiO4 or (M1,M2)TiO4 containing two divalent metal elements M.
[0036] The second crystal phase does not have piezoelectric properties, but by being mixed with the first crystal phase, it improves the sintering property of the lead-free piezoelectric ceramic composition, improves its structural stability, and improves its piezoelectric properties. Specifically, the second crystal phase fills the voids formed between the crystals of the first crystal phase. As a result, the crystals of the first crystal phase are bonded together by the second crystal phase, which is presumably why the structural stability of the lead-free piezoelectric ceramic composition is improved, and why the piezoelectric properties are improved.
[0037] [Internal electrodes 3,4] 2, the internal electrodes 3, 4 are arranged alternately in the stacking direction, and one piezoelectric body 2 is sandwiched between the internal electrodes 3 and 4. The internal electrodes 3 are electrodes of the same polarity (e.g., positive poles) on one side, and the internal electrodes 4 are electrodes of the same polarity (e.g., negative poles) on the other side. The internal electrodes 3, 4 of different polarities are arranged at a distance from each other in the stacking direction so as not to be electrically short-circuited.
[0038] One side edge (the left side in FIG. 1) of the internal electrode 3 is formed in a convex shape so as to be exposed on one side surface (the left side surface in FIG. 1) of the laminate 5. The other side edge (the right side in FIG. 1) of the internal electrode 3 is formed in a straight line so as not to be exposed on the other side surface (the right side surface in FIG. 1) of the laminate 5.
[0039] One side edge (the right side in FIG. 1) of the internal electrode 4 is formed in a convex shape so as to be exposed on the other side surface (the right side surface in FIG. 1) of the laminate 5. The other side edge (the left side surface in FIG. 1) of the internal electrode 4 is formed in a straight shape so as not to be exposed on one side surface (the left side surface in FIG. 1) of the laminate 5.
[0040] By configuring the internal electrodes 3, 4 in this manner, the internal electrodes 3, 4 of different polarities are prevented from being electrically short-circuited with each other.
[0041] [Slit 6] Slits 6 are formed along the entire circumference of the outer circumferential side surface of the laminate 5, perpendicular to the lamination direction (parallel to the lamination surface) and extending a predetermined depth from the outer circumferential side surface. As shown in FIG. 1, the depth of the slits 6 from the outer circumferential side surface of the laminate 5 is set to be deeper than the ends of the internal electrodes 3 and 4. A plurality of slits 6 are formed at arbitrary intervals in the lamination direction, and every 35 layers or less. These slits 6 are formed for the purpose of alleviating the stress applied when the piezoelectric element 1 is driven.
[0042] [Side electrodes 7,8] In addition, side electrodes 7 and 8 are formed on both side surfaces of the laminate 5. These side electrodes 7 and 8 are formed, for example, by patterning a conductive paste using screen printing or the like, and are separated into blocks divided in the laminate direction by slits 6.
[0043] [External electrodes 11,12] Solder layers 9, 10 are formed on the surfaces of the side electrodes 7, 8. A pair of external electrodes 11, 12 are fixed to the side electrodes 7, 8 via the solder layers 9, 10. This allows the side electrodes 7, 8 of each block divided in the stacking direction by the slits 6 to be electrically connected to each other. The external electrodes 11, 12 are made of a conductive material (e.g., copper). The external electrodes 11, 12 are formed, for example, in a mesh shape, and are deformable in response to the expansion and contraction of the laminate 5.
[0044] [Lead electrodes 13, 14] 1, lead electrodes 13, 14 serving as voltage supply members for supplying voltage from the outside are fixed via solder layers 9, 10. Since the lead electrodes 13, 14 are fixed to the side electrodes 7, 8, the external electrodes 11, 12 will not break due to the inertial weight of the lead electrodes 13, 14, etc., even if the laminate 5 is vibrated at high speed for a long period of time.
[0045] The laminate 5 is constructed by alternately laminating multiple layers of piezoelectric bodies 2 and internal electrodes 3, 4, and is composed of a piezoelectric active portion 50 that is displaced by applying a voltage to the internal electrodes 3, 4, and a piezoelectric inactive portion 51 that is not displaced. The piezoelectric inactive portions 51 are disposed on the lower, upper, and outer periphery of the piezoelectric active portion 50.
[0046] 1 is a fixed end that is fixed and does not move, and the upper side is a movable end that moves. Lead electrodes 13, 14 are fixed to side electrodes 7, 8 of a block located at the end on the fixed end side. That is, lead electrodes 13, 14 are fixed to side electrodes 7, 8 on the fixed end side of slit 6, which is closest to the fixed end side.
[0047] [Stress relief section 30] 3 is a cross section of the internal electrode 3 of the laminate 5 cut in a direction perpendicular to the lamination direction. Since the cross section of the internal electrode 4 is similar to the cross section of the internal electrode 3, it is not shown in the figure, and the cross section of the internal electrode 3 will be described below as a representative example.
[0048] The outer edge of the cross section of the internal electrode 3 has four sides 20 and four stress relief parts 30 that connect each pair of adjacent sides 20. When the point where the extensions 21 of each pair of adjacent sides 20 intersect is defined as a virtual vertex 22, the stress relief parts 30 are formed so as to be located closer to the center of the internal electrode 3 than the virtual vertex 22. The stress relief parts 30 are in the shape of a quadrant and are formed of a curved surface that is convex outward. The stress relief parts 30 are arranged corresponding to the four corners of the internal electrode 3, and four in total are provided. The cross section of the internal electrode 3 in this embodiment is substantially square, but may be substantially triangular or substantially polygonal with five or more sides.
[0049] [Method of manufacturing piezoelectric element 1] An example of a method for manufacturing the piezoelectric element 1 is shown below. Necessary raw material powders of the main phase are selected and weighed to obtain the desired composition. The raw material powders may be oxides, carbonates, or hydroxides of the elements contained in the main phase. Ethanol is added to these raw material powders, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. The resulting slurry is dried, and the resulting mixed powder is calcined, for example, in air at 600 to 1100°C for 1 to 10 hours to obtain a calcined product of the main phase.
[0050] Necessary raw powders of the subphase are selected and weighed to obtain the desired composition. The raw powders may be oxides, carbonates, or hydroxides of the elements contained in the subphase. Ethanol is added to these raw powders, and the mixture is wet-mixed in a ball mill for preferably 15 hours or more to obtain a slurry. The resulting slurry is dried, and the resulting mixed powder is calcined, for example, at 600 to 1100°C in an air atmosphere for 1 to 10 hours to obtain a calcined product of the subphase.
[0051] The obtained calcined main phase and subphase products are weighed to obtain the desired composition, and a dispersant, a binder, and an organic solvent such as toluene are added to the mixture, which is then pulverized and mixed to form a slurry.Then, the mixture is processed into a sheet shape using a doctor blade method or the like to produce a ceramic green sheet.
[0052] Next, using a conductive paste for internal electrodes, unfired electrodes that will become internal electrodes are formed on the surfaces of the ceramic green sheets by, for example, screen printing.
[0053] Next, a plurality of ceramic green sheets with unsintered electrodes formed thereon are laminated, and then ceramic green sheets without unsintered electrodes are laminated on both sides of the laminate, and the laminate is pressed to obtain a pressed body. After cutting the pressed body into a desired shape, the pressed body is subjected to a binder removal treatment, for example, by holding the pressed body at 200 to 400°C for 2 to 10 hours.
[0054] The pressed body after the binder removal process is fired, for example, at 1000 to 1200°C for 2 to 5 hours in a reducing atmosphere with an oxygen partial pressure adjusted so that the unfired electrodes do not oxidize, to obtain a laminate. At this time, the distribution of the subphase made of an oxide containing manganese can be controlled by adjusting the firing temperature, holding time, and other conditions according to the composition.
[0055] External electrodes made of Au are formed on the side surfaces of the obtained laminate by, for example, sputtering, to obtain the piezoelectric element 1.
[0056] The above-mentioned manufacturing method is an example, and various other steps and processing conditions can be used for manufacturing the piezoelectric element 1. For example, instead of separately producing the calcined products of the main phase and the subphase and then mixing and firing the powders of both, the raw materials may be mixed in a quantity ratio according to the final composition of the lead-free piezoelectric ceramic composition, and then fired. However, according to the method of separately producing the calcined products of the main phase and the subphase and then mixing them, the composition of the main phase and the subphase can be more strictly controlled, and therefore the yield of the lead-free piezoelectric ceramic composition can be increased.
[0057] [Effects of embodiment 1] The piezoelectric element 1 of the present disclosure is a piezoelectric element 1 in which a piezoelectric body 2 formed of a lead-free piezoelectric ceramic composition having piezoelectric properties and internal electrodes 3, 4 are alternately stacked in multiple layers, and the outer edge of a cross section of the piezoelectric element 1 cut in a direction perpendicular to the stacking direction of the internal electrodes 3, 4 has a plurality of sides 20 and a plurality of stress relief portions 30 each connecting each pair of adjacent sides 20, and the stress relief portions 30 are formed so as to be located closer to the center of the internal electrodes 3, 4 than the virtual vertex 22, when the point where the extended portions 21, 21 of each pair of adjacent sides 20, 20 intersect is defined as a virtual vertex 22.
[0058] The piezoelectric body 2 in the portion sandwiched between the internal electrodes 3, 4 and the adjacent internal electrodes 4, 3 becomes the piezoelectric active portion 50, and the portion not sandwiched between the internal electrodes 3, 4 becomes the piezoelectric inactive portion 51. It is known that the displacement distribution in the boundary portion between the piezoelectric active portion 50 and the piezoelectric inactive portion 51 changes significantly, particularly near the corners of the internal electrodes, and stress is concentrated in this portion. In addition, the piezoelectric body 2 formed of the lead-free piezoelectric ceramic composition is less likely to deform and has a higher rigidity than PZT, so it is considered that stress is more concentrated therein. According to the above configuration, the corners of the internal electrodes 3, 4, where stress is concentrated during piezoelectric driving, are formed in a curved shape, thereby realizing stress relaxation in the piezoelectric active portion 50 compared to conventional lead-free piezoelectric laminates. This makes it possible to provide a piezoelectric element 1 that suppresses the occurrence of delamination and cracks during piezoelectric driving and improves reliability.
[0059] The stress relaxation portion 30 is configured with an outwardly convex curved surface. Since the stress relaxation section 30 is composed of a curved surface that is convex outward, it is possible to achieve stress relaxation for the piezoelectric active section 50 while minimizing the deterioration of piezoelectric characteristics due to a decrease in electrode coverage, thereby providing a piezoelectric element 1 with improved reliability.
[0060] <Embodiment 2> Next, a second embodiment of the present disclosure will be described with reference to FIG. 4. The piezoelectric element 100 of the second embodiment is the same as that of the first embodiment except that the shape of the stress relaxation portion 30 of the internal electrodes 3 and 4 is changed. Since the other configurations are the same as those of the first embodiment, a duplicated description will be omitted. The same reference numerals will be used for the same configurations as those of the first embodiment, and the numerals with 100 added to the numerals will be used for the configurations corresponding to those of the first embodiment. FIG. 4 is a cross section of the internal electrode 103 of the laminate 105 cut in a direction perpendicular to the lamination direction. The cross section of the internal electrode 104 is the same as that of the internal electrode 103, so its illustration will be omitted, and the cross section of the internal electrode 103 will be representatively described below.
[0061] The outer edge of the cross section of the internal electrode 103 has four sides 120 and four stress relief parts 130 that connect each pair of adjacent sides 120. When the point where the parts 121, 121 that are extended from each pair of adjacent sides 120, 120 intersect is defined as a virtual vertex 122, the stress relief parts 130 are formed so as to be located closer to the center of the internal electrode 103 than the virtual vertex 122. The stress relief parts 130 are formed in a quadrant shape and are curved to be convex inward. The stress relief parts 130 are arranged corresponding to the four corners of the internal electrode 103, and four in total are provided. The cross section of the internal electrode 103 in this embodiment is substantially square, but may be substantially triangular or substantially polygonal with five or more sides.
[0062] <Embodiment 3> Next, a third embodiment of the present disclosure will be described with reference to FIG. 5. The piezoelectric element 200 of the third embodiment is obtained by changing the shape of the stress relaxation portion 30 of the internal electrodes 3 and 4 of the first embodiment, and other configurations are the same as those of the first embodiment, so that a duplicated description will be omitted. The same reference numerals will be used for the same configurations as those of the first embodiment, and reference numerals with 200 added to the numerals will be used for configurations corresponding to those of the first embodiment. FIG. 5 is a cross section of the internal electrode 203 of the laminate 205 cut in a direction perpendicular to the lamination direction. The cross section of the internal electrode 204 is similar to the cross section of the internal electrode 203, so illustration will be omitted, and the cross section of the internal electrode 203 will be described below as a representative.
[0063] The outer edge of the cross section of the internal electrode 203 has four sides 220 and four stress relief parts 230 that connect each pair of adjacent sides 220. When the point where the parts 221, 221 that are extended from each pair of adjacent sides 220, 220 intersect is defined as a virtual vertex 222, the stress relief parts 230 are formed so as to be located closer to the center of the internal electrode 203 than the virtual vertex 222. The stress relief parts 230 are formed of a C-face that forms a tapered shape. The stress relief parts 230 are arranged corresponding to the four corners of the internal electrode 203, and four in total are provided. The cross section of the internal electrode 203 in this embodiment is substantially square, but may be substantially triangular or substantially polygonal with five or more sides.
[0064] <Other embodiments> (1) In the above embodiments 1 to 3, the piezoelectric element 1 has multiple piezoelectric bodies 2 and multiple internal electrodes. However, the piezoelectric element may have a single-layer structure having one piezoelectric body 2 and two internal electrodes arranged on either side of the piezoelectric body 2.
[0065] (2) In the above first to third embodiments, the stress absorbing portion is formed of a curved surface or a C-surface, but the shape of the stress absorbing portion is not important as long as the stress absorbing portion is located closer to the center of the internal electrode than the virtual vertex. [Explanation of symbols]
[0066] 1, 100, 200: Piezoelectric element 2: Piezoelectric body 3, 103, 203: Internal electrode 4, 104, 204: Internal electrode 5, 105, 205: Laminated body 6: Slit 7: Side electrode 8: Side electrode 9: Solder layer 10: Solder layer 11: External electrode 12: External electrode 13: Lead electrode 14: Lead electrode 20: Side 21: Extension of each pair of adjacent sides 22: Virtual vertex 30, 130, 230: Stress relief section 50: Piezoelectrically active portion 51: Piezoelectrically inactive portion
Claims
1. A piezoelectric element in which a piezoelectric body formed of a lead-free piezoelectric ceramic composition and an internal electrode are alternately laminated in a plurality of layers, an outer edge of a cross section of the piezoelectric element, the cross section being obtained by cutting the internal electrode in a direction perpendicular to the lamination direction, has a plurality of sides and a plurality of stress relaxation portions each connecting a pair of adjacent sides; A piezoelectric element, wherein the stress relaxation portion is formed so as to be located closer to the center of the internal electrode than a virtual vertex defined as the point where the extensions of each of a pair of adjacent sides intersect.
2. The piezoelectric element according to claim 1 , wherein the stress relaxation portion is formed of an outwardly convex curved surface.
3. The piezoelectric element according to claim 1 , wherein the stress relaxation portion is formed of an inwardly convex curved surface.
4. The piezoelectric element according to claim 1 , wherein the stress relaxation portion is configured with a C-face forming a tapered shape.
Citation Information
Patent Citations
Method of manufacturing lamination-type piezoelectric actuator
JP2011181958A